Microwave assisted synthesis of a mono organoimido functionalized Anderson polyoxometalate. Issue 48 (19th November 2015) - Ritchie, C.; Bryant, G.
Abstract : The synthesis of an aliphatic organoimido functionalized polyoxometalate has been achieved through a microwave assisted reaction protocol in the absence of any activating reagents. Abstract : The synthesis of an aliphatic organoimido functionalized polyoxometalate has been achieved through a microwave assisted reaction protocol in the absence of any activating reagents. Characterization of the pendant amine containing polyanion [Mo6 O18 NC(OCH2 )3 MnMo6 O18 (OCH2 )3 CNH2 ] 5− (1) includes single crystal XRD, NMR, ESI-MS, IR and SAXS.